EVALUATION OF THE ISLAMIC SPIRITUAL GUIDANCE PROGRAM IN THE SPECIAL COACHING INSTITUTION FOR CHILDREN CLASS I TANGERANG - Amaludin, Reki Akbal (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Children in the Special Child Development Institution (LPKA) are in an institution intended for children who are or will be serving a criminal term. The institution provides spiritual formation for correctional students, aiming to enhance their religious knowledge as a fundamental step towards becoming good individuals. Program evaluation, according to Tyler is a process that aims to find out whether educational goals or programs have been realized or not. Evaluation of the Islamic spiritual guidance program carried out in special institutions for child development is carried out by direct observation to see the actual situation in the field. The evaluation is carried out to assess how effective the program is. An evaluation of this Islamic spiritual development program is vital to support decision-making that this program is essential for the children assisted at LPKA and can facilitate the progress of formation at LPKA if the program runs well, because the basis of the guidance carried out is in line with the objectives of LPKA development. Keywords: Evaluation; LPKA; Assisted Child